Superconductors Materials, Properties and Applications - Gabovich, Alexander (IntechOpen, 2012)
The book includes 17 chapters written by noted scientists and young researchers and dealing with various aspects of superconductivity, both theoretical and experimental. The authors tried to demonstrate their original vision and give an insight into the examined problems. A balance between theory and experiment was preserved at least from the formal viewpoint (9 and 8, respectively). The readers should be warned that many of the problems studied here are far from being solved and are treated on the basis of competing viewpoints. The reason is that such is the state of the art! Science of superconductivity develops rapidly and new unexpected discoveries are expected in the nearest future.